Reconstructing the Islamic Religious Education Curriculum with a Bullying Prevention Perspective - Hasan, Moch. Sya'roni; Azizah, Mar'atul (Pascasarjana Universitas KH. Abdul Chalim, 2022)
This study examines the reconstruction of the Islamic Religious Education (PAI) curriculum as a strategy to prevent bullying in SMA Primaganda. The problem of bullying in schools is a serious issue that requires special attention. The hypothesis is that the integration of anti-bullying values ​​in the PAI curriculum will be effective in reducing bullying incidents in schools. This study uses a case study method with a qualitative approach, involving in-depth interviews with PAI teachers, students, and education experts, participant observation, and analysis of curriculum documents. The results of the study indicate that the reconstruction of the PAI curriculum that integrates anti-bullying values ​​has succeeded in reducing bullying incidents in schools. This success was achieved through systematic implementation that included the development of learning modules, teacher training, and collaborative activities. A holistic approach involving the dimensions of moral knowledge, moral feelings, and moral actions has proven effective in increasing students' awareness and understanding of the negative impacts of bullying. The continuous evaluation system confirms the creation of positive changes in school culture, marked by increased empathy and cooperation among students. The findings of the study indicate that the integration of anti-bullying values ​​in the PAI curriculum is not only effective in preventing bullying but also contributes to the formation of positive student character and the creation of a safe and inclusive learning environment. This curriculum reconstruction model can be a reference for other educational institutions in developing effective bullying prevention programs.